Blueprint : Intelligent phone case / Muhammad Ikmal Johari… [et al.] - Johari, Muhammad Ikmal; Kasim, Muhammad Ghazali; Jailani, Muizzuddin; Rahman, Nurul Liyana; Kamaruzaman, Kamalina Azyyati
The product to be developed is Intelligent Phone Case. It is known the phone tend to fall and broke down. Thus, the team want to introduce the new high quality casing phone with many benefit and Eco-Green. This casing phone provide many design of wallpaper for phone case by changing it with only one button. Besides, this intelligent phone case is secured with safety by providing anti-fall system, advanced hands grip and others.